Epileptiform syndrome in rats produced by injecting tetanus toxin into the hippocampus. Issue 4 (April 1977) - Mellanby, J; George, G; Robinson, A; Thompson, P
Abstract : An epileptiform syndrome in rats produced by injecting small doses (a few (mouse)LD50) of tetanus toxin into the hippocampus is described. The animals had intermittent seizures, with at least a superficial resemblance to human epilepsy, for some weeks but they eventually recovered. They were hyperkinetic for several weeks after the injection of toxin, and showed intermittent aggressive behaviour. Control animals which received similar injections of tetanus toxin first neutralised with antitoxin did not have seizures, and their behaviour appeared normal. EEG recordings showed characteristic seizure activity. Histological examination of the site of injection showed very little morphological damage.